USING OF ONION ARCHITECTURE WITHIN THE SUBJECT-ORIENTED APPROACH - NIKONOV, OLEH; SKIDAN, VLADYSLAVA; VOLIVACH, ANTONINA; MAMONTOV, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
As a result of the Onion-architecture research in a subject-oriented approach, the effectiveness of using subject-oriented design, as well as Onion architecture, was analyzed. It was found that when developing a project based on a subject-oriented approach, the key aspect is the creation of a reliable model of the subject area. It is also established that the process of creating this model for a specific problem is an iterative collaboration between business experts and the technical team. It was determined that during the software development process, emphasis is placed on increasing its flexibility, facilitating communication between members of the development team and emphasizing the importance of the subject area of the future system. It is proposed to use a subject-oriented approach for the development of business process automation systems, as well as for the development of integrations for business process automation systems. The advantages of using a subject-oriented approach in the context of business process automation systems have been researched. The conducted studies allow us to assess the advantages and challenges of using a subject-oriented approach during the development of business process automation systems and integrations for them, which is important for development teams. The obtained results are the basis for future research and effective implementation of business process automation systems and integrations for them. For future research, it is suggested to focus on the prospects for the development of a subject-oriented approach, in particular, on taking into account modern trends and forecasting possible changes in the business environment. Looking ahead, it is recommended that future research delves deeper into the evolving landscape of subject-oriented approaches. Specifically, attention should be directed towards staying abreast of modern trends in technology and business practices. By forecasting potential changes in the business environment, development teams can proactively adapt their strategies, ensuring the continued relevance and effectiveness of subject-oriented approaches in the realm of business process automation. This forward-looking approach will contribute to the ongoing refinement and optimization of systems, aligning them with the dynamic needs of the contemporary business.